Russian demographic tradition at the university level: Current educational and managerial tasks and solutions - O. A. Yastrebov; T. K. Rostovskaya (RUDN journal of Sociology)
In recent decades, the Russian society has experienced complex demographic processes caused by both objective factors of a global nature (population aging, declining birth rate, demographic transition, transformation of values and priorities of younger generations in the context of digitalization, unbalanced migration flows, etc.) and peculiarities of the social-economic and political-ideological development of the post-Soviet space (external ideological influence, unresolved issues accumulated during the Soviet period, ongoing education reforms, multiconfessional and multinational living space with many local and regional combinations of group and collective priorities, etc.). The state recognized the importance of demographic issues for ensuring national security by adopting policy documents to improve demographic indicators not only with financial means but also by setting clear value priorities for family and demographic policies for the long term. However, it is impossible to ensure demographic stability and security of the Russian society only with targeted efforts “from above” - it is necessary to consolidate the work of government agencies, scientific and educational institutions. Based on their specialized expert experience, the authors outline possible areas of such consolidation at three levels of social management - government target programs and national projects (conditional macro-level), expansion of professional horizons of young people through the inclusion of a historical and general demographic component in specialist training programs (conditional micro-level) and supplementation of the corporate culture of specific organizations with demographic issues (conditional meso-level). The article focuses, first, on possible strategies for including the corpus of demographic knowledge (and the corresponding block of demographic topics or disciplines) in the higher education curricula (research issues, thematic emphases, recommended literature, ideological component, etc.); second, on the need to introduce demographic issues into the system of corporate responsibility. The RUDN University is presented as an illustrative “case” that is actively rather than declaratively develops the demographic component in the Russian higher education and has already implemented a set of measures for corporate demographic policy in the system of the strategic university management.